Boundary element analysis of fibre bridging in perforated fibre metal laminates - Tan, Benjamin Jun Jie (Nanyang Technological University, 2023)
Fibre metal laminate (FML), a type of material created by sandwiching a fibre laminate between two metal alloys, has been seeing increasing utilisation within the aerospace industry due to its improved weight and strength. Crack propagation thus becomes a critical component in the study of this material in this industry. A review on the linear elastic fracture mechanics, fibre-bridging mechanism, and theoretical analysis of perforation on FML will be done in this study. This study will make use of Boundary Element Methods (BEM) to analyse the different factors, including extent of fibre-bridging, crack geometries, crack sizes and delamination shapes, that affect the stress distributions and normalised stress intensity factor (SIF) at the crack-tip. The use of BEM replaces the need for more computationally intensive methods such as finite element analysis in obtaining of these results. Using the results collected, this study was able to conclude in general that an increase in crack size ratios led to increase in stress distribution and normalised SIF, while a decrease in extent of fibre-bridging led to increases in stress distributions and normalised SIF.